The prevalence, detection and prognosis of atrial fibrillation in patients with transient ischaemic attack and stroke - Yiin, G; Dr Gabriel Shih Chung Yiin (2014)
Stroke is a major cause of premature death and disability throughout the world and atrial fibrillation (AF) is one of the most common preventable causes of stroke. AF affects about 10% of individuals aged ≥80 years, but warfarin is substantially under-used in this age group despite being effective in preventing AF-related thromboembolic events. AF-related ischaemic strokes tend to be severe and incur high care costs, and non-cerebral systemic embolism secondary to AF is also a major clinical burden. Despite that, there are few population-based studies on AF-related ischaemic stroke, and no recent study of the burden of AF-related thromboembolism and the population impact of under-treatment. I have used data from the Oxford Vascular Study (OXVASC), a prospective, population-based incidence study of vascular disease in all territories, which was started in April 2002 and is on-going. The study population comprises of 92,728 individuals registered with 100 family physicians in nine general practices and uses multiple overlapping methods of “hot” and “cold” pursuit to achieve near-complete ascertainment of all patients with acute vascular events. There are several findings described by the research in this thesis which have important implications for public health and can be utilised to improve secondary prevention in stroke. First, I have shown that one-third of all incident embolic events were related to AF and 60% of AF-related embolic events occurred at ≥80 years. Second, I have shown that only 9% of patients aged ≥80 years with incident embolic event related to known prior AF were on premorbid warfarin, and consequently three quarters of those previously independent were dead or disabled six months post event. Third, I have shown that there has been no reduction in age-specific incidence of AF-related ischaemic stroke in Oxfordshire over the last 25 years. Fourth, I have shown that assuming age-specific incidence does not continue to rise, if prevention is not improved, the number of embolic events at age ≥80 years would be expected to treble by 2050 (72,975 AF-related embolic events), with 84% of events at all ages occurring at age ≥80. Fifth, I have shown through a meta-analysis that one in five incident strokes had a history of prior AF of which only 19% were on premorbid warfarin, and AF was related to one in three incident ischaemic strokes. Sixth, I have shown that 1 in 5 stroke patients with known prior AF subsequently became institutionalised and incurred high acute and long-term care costs. Seventh, I have shown that one in five patients with undetermined cerebral ischaemic event subsequently had AF-related late recurrent stroke. Eighth, I have shown that even though TIA or ischaemic stroke patients who subsequently turned out to have new AF at follow-up had significantly higher baseline NT-proBNP compared to non-AF group, its utility is limited by low sensitivity and specificity. Ninth, I have shown in another meta-analysis that the duration of cardiac monitoring after cerebral ischaemic events was the main determinant of the observed rate of pAF, and that 5-7 days of monitoring may be adequate in unselected patient populations. Finally, I have shown that using 5-day event loop recording in clinic patients with TIA and minor ischaemic stroke could detect 12% new AF and the delay in monitoring did not reduce the sensitivity of pAF detection.